Active wheat gluten films obtained by thermoplastic processing - Ansorena, Maria Roberta (2016)
Active films based on glycerol-plasticized wheat gluten protein containing different thyme oil concentrations (0-15 wt.%) were prepared by a thermoplastic process involving relatively high temperature and pressure. A complete thermal, structural, mechanical, antimicrobial and antioxidant characterization of all formulations was carried out. Antimicrobial activity tests showed that neat thyme oil presented a meaningful antimicrobial activity. The addition of thyme essential oil to formulations based on gluten protein allowed to prepare biodegradable and edible films with increased in vitro antioxidant and antimicrobial properties for the most concentrated samples. However, increasing essential oil concentration led to a continuous decrease in the tensile and storage modulus but to an increase in the deformability of the films. Only films containing 10 and 15 wt.% thyme oil showed reduced moisture sorption with respect to the control film (0% thyme oil), while the water vapor permeability and total soluble matter were not markedly affected by its addition. These changes were attributed to the interference of the oil in the formation of the protein molecular network, and were corroborated by the analysis of the films microstructures by SEM.